PELAKSANAAN PERJANJIAN KERJASAMA PEMANFAATAN BARANG MILIK DAERAH PEMERINTAH KOTA PEKANBARU DENGAN PT. AGUNG RAFA BONAI - Syauqi Sepriza; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Build-Use-Transfer is the utilization of State/Regional Property in the form of land by another party byconstructing buildings and/or facilities along with their facilities, then utilized by the other party within a certainagreed period of time, to be subsequently handed back the land along with the building and/or facilities and facilitiesafter the expiry of the term. PT. Agung Rafa Bonai (PT. ARB) was unable to fulfill his achievement, namelycompleting the construction of the Pekanbaru City main market within 24 months according to the contract agreedwith the Pekanbaru City Government. The purpose of writing this thesis First is to find out the implementation of thecooperation agreement for the use of regional property owned by the Pekanbaru City Government and PT. ARB,Third, to find out the legal consequences of default in the implementation of the cooperation agreement for the use ofregional property, the Pekanbaru City Government and PT. ARB.This research is classified in the type of empirical juridical research, namely research on the effectivenessof the law, how the law operates in society. This research was conducted at the Office of Industry and Trade ofPekanbaru City and PT. ARB, while the sample population is the Head of the Pekanbaru City Industry and TradeOffice and the Director of PT. ARB with the problems studied in this study, the data sources used, primary data andsecondary data, data collection techniques in this study with interviews, literature review, and data analysis.The conclusion of this study. First, the implementation of the cooperation agreement for the use of regionalproperty, the Pekanbaru City Government and PT. ARB, namely the PT. ARB was unable to fulfill its achievements,namely completing the construction of the Pekanbaru City main market within 24 months, paying annualcontributions for 3 consecutive years and not ensuring cleanliness in the main market project development area. Thetwo obstacles in the implementation of the cooperation agreement for the use of regional property, the PekanbaruCity Government and PT. ARB is the Covid-19 pandemic which has an impact on the company so that the company'sactivities are not smooth, especially related to development and this has an impact on the budgeting of funds thathave been prepared previously. PT. ARB selling assets to continue the development of the main market has not beenimplemented. Third, the legal consequences of default in the implementation of the cooperation agreement for the useof regional property owned by the Pekanbaru City Government and PT. ARB means that the Pekanbaru CityGovernment has not carried out the legal consequences in accordance with Article 19 concerning the termination ofthe contract. The Pekanbaru City Government may terminate the BGS unilaterally in accordance with Article 19 ofthe cooperation contract. However, the Pekanbaru City Government still provides opportunities for PT. ARB to fulfillits obligations in completing the Pekanbaru City main market.